Floristic composition of the Seasonal Semideciduous Forest in Southern Brazil: Reserva Biológica das Perobas, State of Paraná - Greta Aline Dettke; Laianne Mayara Pezenti Crespão; Luciana Veríssimo Siquerolo; Edemilson Luiz Siqueira; Marcelo Galeazzi Caxambú (Acta Scientiarum. Biological Sciences, 2018)
This study catalogued the vascular species found in the second largest continuous remnant of Seasonal Semideciduous Forest in the State of Paraná. A total of 425 species distributed among 295 genera and 101 families were identified. The most representative families are Fabaceae (27 species), Asteraceae (21), Bignoniaceae (19), Poaceae (19) and Orchidaceae (15). Two species are unique records in the State of Paraná, in the study area: Bulbophyllum rupicolum Barb.Rodr. (Orchidaceae) and Heladena multiflora (Hook. & Arn.) Nied. (Malpighiaceae). The predominant life forms are herbs and trees, and terrestrial plants represented the majority of species. We recorded 11 exotic species. It is a large remnant and contains high specific diversity for the region, with a quarter of the species listed for the Seasonal Semideciduous Forest of the State of Paraná.